Diet Quality, Protein Quality, and Micronutrient Adequacy of Myanmar Vegans and Lacto-Ovo-Vegetarians - Kyi, Su Mon; Prachansuwan, Aree; Kriengsinyos, Wantanee; Pongcharoen, Tippawan (Journal of Nutrition Association of Thailand (Online), 2024)
This study evaluated dietary quality, protein quality, and micronutrient adequacy among vegans, lacto-ovo-vegetarians (LOVs), and omnivores in Myanmar using the Healthy Eating Index-2015 (HEI-2015), the digestible indispensable amino acid score (DIAAS), as well as probability of adequacy (PA) and mean PA (MPA) for vital nutrients like proteins, vitamin B12, calcium, iron and zinc. A purposive sample of 97 participants (34 vegans, 32 LOVs, 31 omnivores) provided three-day food records. Results showed that HEI scores were not significantly different between groups (omnivores: 58.6 ± 9.8, vegans: 56.9 ± 11.1, LOVs: 55.0 ± 12.2; p = 0.441). Omnivores exhibited the highest DIAAS, PA, and MPA scores in addition to achieving excellent protein quality (DIAAS > 100%), while vegans and LOVs achieved good quality (75-99%) or poor quality protein (< 75%). Median PAs for calcium among all groups were uniformly 0%. Omnivores had the highest median PAs for zinc (100%) and iron (85%), while vegans and LOVs had median PAs between 0-0.5% (p < 0.001). MPA for micronutrients was 57.7 (41.7, 65.3) % for omnivores, compared to 0.2 (0.1, 0.9) % for LOVs and 0.2 (0.1, 0.8) % for vegans (p < 0.001). This study underscores the need for Myanmar vegans and LOVs to diversify protein sources and include calcium, zinc, and iron-rich plant foods and supplements. For LOVs, increased dairy consumption can offer a viable calcium source. These findings provide essential insights for tailoring nutritional recommendations for diverse dietary patterns in Myanmar.